Explaining the topic of vitamins for 7th graders through a project-based teaching method - Maksud Ravshanov; Khurshida Tursunova; Laylo Kholiyeva (Science and Education, 2026)
This article explores the implementation of a project-based learning (PBL) method for teaching the topic of vitamins to 7th-grade students. PBL is a dynamic classroom approach that actively engages students in real-world, meaningful projects, fostering deeper understanding and retention of scientific concepts. By integrating inquiry, collaboration, and creativity, PBL transforms abstract topics like vitamins into tangible, experiential learning. This article discusses the theoretical foundations of PBL, outlines a detailed project framework for teaching vitamins, and reflects on the pedagogical benefits, including enhanced critical thinking, interdisciplinary connections, and lifelong healthy habits.